Husband and Wife Perspectives on Farm Household Decision-making Authority and Evidence on Intra-household Accord in Rural Tanzania. (February 2017) - Anderson, C. Leigh; Reynolds, Travis W.; Gugerty, Mary Kay
Highlights: We use surveys of husbands and wives in Tanzania to explore rural household decision-making. We find perceptions of household decision-making authority differ depending on the spouse asked. Factors associated with a wife's authority include age, education, health, children, and labor hours. The allocation of intra-household authority also varies across thirteen different decision questions. A lack of "intra-household accord" over authority may be a barrier to empowerment efforts. Summary: We use OLS and logistic regression to investigate variation in husband and wife perspectives on the division of authority over agriculture-related decisions within households in rural Tanzania. Using original data from husbands and wives (interviewed separately) in 1, 851 Tanzanian households, the analysis examines differences in the wife's authority over 13 household and farming decisions. The study finds that the level of decision-making authority allocated to wives by their husbands, and the authority allocated by wives to themselves, both vary significantly across households. In addition to commonly considered assets such as women's age and education, in rural agricultural households women's health and labor activities also appear to matter for perceptions of authority. We also find husbands and wives interviewed separately frequently disagree with each other over who holds authority over key farming, family, and livelihood decisions. Further, the results of OLS and logistic regression suggest that even after controlling for various individual, household, and regional characteristics, husband and wife claims to decision-making authority continue to vary systematically by decision—suggesting that decision characteristics themselves also matter. The absence of spousal agreement over the allocation of authority (i.e., a lack of "intra-household accord") over different farm and household decisions is problematic for interventions seeking to use survey data to develop and inform strategies for reducing gender inequalities or empowering women in rural agricultural households. Findings provide policy and program insights into when studies interviewing only a single spouse or considering only a single decision may inaccurately characterize intra-household decision-making dynamics.